Repositioning and Fixation of an Intruded Immature Permanent Tooth in a Pediatric Dental Trauma Case - Nelwan, Sindy Cornelia; Putri, Sofia Tandya; Prima, Nuryati; Ramakrishnan, Krishna Kumar (Indonesian Journal of Dental Medicine, 2025)
Background: Intrusive luxation is one of the most severe types of dental trauma, especially in children with immature permanent teeth. Immediate and appropriate management is crucial to preserve pulp vitality and ensure proper root development. Purpose: This case report aims to present the management of an intruded immature permanent maxillary incisor in a pediatric patient through surgical repositioning and flexible splinting. Case: An 8-year-old boy presented three days after a football-related fall with a 6 mm intrusion of the permanent maxillary right central incisor. The tooth showed no mobility, and no root fracture was detected radiographically, although the periodontal space was reduced. Case Management: Due to the severity of the intrusion, immediate surgical repositioning under local anesthesia was performed. The tooth was carefully luxated and repositioned, followed by splinting using brackets and ligature wire from tooth #54 to #63 for three weeks. Antibiotics, analgesics, and antiseptic mouth rinse were prescribed. The tooth was kept out of occlusion, and pulp testing at three weeks indicated vitality. The splint was removed without complications, and a five-month follow-up confirmed stable teeth, an asymptomatic condition, and ongoing root and periodontal healing. Conclusion: Early surgical repositioning combined with flexible splinting can yield favorable outcomes in managing intrusive luxation in immature permanent teeth. Timely intervention and continuous follow-up are essential to preserve pulp vitality, support root development, and prevent complications such as resorption and ankylosis.